Victimisation and fear of crime in Brazil: The effect on the desire to move - Plassa, Wander (Journal of criminology, 2023)
We examined the effect of victimisation and fear of crime in Brazil and its attendant influence on the desire to move. Data drawn from the 2012 National Victimisation Survey were used to model the relationship between victimisation and the desire to move, with fear of crime used as a mediator variable. Our results indicate that being a victim of crime leads to increased fear, which, in turn, increases the desire to move. However, the indirect effect is comparatively small (i.e., our mediator variable?fear of crime?only marginally attenuates the relationship between victimisation and the desire to move). We also found evidence that property victimisation, victimisation occurring close to an individual's home, and indirect victimisation (i.e., hearing about a crime committed against another person in the neighbourhood) were also predictors of an increased desire to move in Brazil. Lastly, our results also suggest the importance of distinguishing between victimisation that occurred in the last 12 months compared to victimisation that occurred more than 12 months ago. Thus, policies that reduce victimisation and fear of crime may minimise the desire to move and any related economic and social costs.